Technological, Organizational, and Environmental Factors and Their Effect on SMEs Performance via Social Media - Yuliani Yuliani; Yopi Yudha Utama (Fenomena, 2024)
Globalization and digitalization have intensified competition, presenting challenges and opportunities for SMEs. While social media (SM) offers significant benefits for enhancing performance, empirical evidence on its mediating role between organizational drivers and outcomes remains limited. Furthermore, research applying the Technological-Organizational-Environmental (TOE) framework in this context is relatively novel. This study examines the effect of TOE factors on SME performance through social media. Using a quantitative approach, data were collected via questionnaires from 384 SMEs in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that technological, organizational, and environmental factors significantly influence social media adoption and SME performance, with technology having the most substantial effect. Social media use also mediates the relationship between TOE and performance. All constructs demonstrated high reliability and validity. The study concludes that improving technological infrastructure, organizational readiness, and environmental awareness—coupled with strategic social media use—can substantially enhance SME performance. These findings provide valuable insights for SMEs and policymakers aiming to leverage digital tools for business growth. Globalisasi dan digitalisasi telah memperketat persaingan, menciptakan tantangan dan peluang bagi Usaha Kecil dan Menengah (UKM). Meskipun media sosial (SM) menawarkan banyak keuntungan untuk meningkatkan kinerja, bukti empiris mengenai perannya sebagai mediator antara kerangka Technological-Organizational-Environmental (TOE) dan kinerja UKM masih terbatas. Penelitian ini bertujuan untuk menganalisis pengaruh langsung dan tidak langsung faktor TOE terhadap kinerja UKM melalui penggunaan media sosial. Dengan pendekatan kuantitatif, data dikumpulkan melalui kuesioner dari 384 UKM di Indonesia. Data dianalisis menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM). Hasil penelitian menunjukkan bahwa faktor teknologi, organisasi, dan lingkungan berpengaruh signifikan terhadap adopsi media sosial dan kinerja UKM, dengan teknologi memiliki pengaruh terkuat. Penggunaan media sosial tidak hanya langsung meningkatkan kinerja tetapi juga secara signifikan memediasi hubungan antara faktor TOE dan kinerja. Disimpulkan bahwa peningkatan infrastruktur teknologi, kesiapan organisasi, kesadaran lingkungan, yang terintegrasi dengan strategi media sosial yang konsisten, sangat penting untuk kinerja UKM yang unggul di era digital.